Teachers’ Roles in Designing and Implementing Numeracy-Oriented Instruction in Junior High School Mathematics: A Multiple Case Study - Rafiq Zulkarnaen; Asya Khaula Aziza (MASI Mandiri Edukasi, 2026)
This study investigates the role of mathematics teachers in junior high schools in promoting students' numeracy through the design and delivery of classroom instruction. The qualitative multiple-case study design was used to gather information on ten mathematics teachers, selected through purposive sampling based on teaching experience and willingness to participate, in the form of lesson plans, observations in classrooms, semi-structured interviews, and analysis of students’ work, which were analyzed using a numeracy framework consisting of representation, conceptual understanding, procedural fluency, and reasoning, guiding thematic content analysis and cross-case comparison. The results show that educators have progressively incorporated real-life contexts and diagnostic tests in their instructional planning. Nevertheless, the combination of the various representations and the systematic development of mathematical reasoning is underdeveloped. These trends indicate that the primary problem with numeracy learning is not the accessibility of numeracy-related tasks, but rather the representation, reasoning, and coherence of instructional design. Based on this, the research indicates the need for professional development initiatives that specifically assist teachers in crafting exploratory, discourse-based numeracy assignments that are consonant with Minimum Competency Assessment (AKM) requirements and classroom contexts.